“Bhimdhunga” and its Driving Force: Analysis with Reflection of the Pokhara Valley Formation, Nepal - Pokharel, Ramjee Prasad (The Himalayan Geographers, 2025)
The Pokhara Valley, located in the southern foothills of the Himalayas, has a complex geological history shaped by tectonic movements, glacial activity, and catastrophic natural events. Among its significant geological features Bhimdhunga (giant boulder), a massive rock weighing 1,439.37 tons, which raises important questions about its transportation from the Annapurna region to its present location. This study investigates the forces responsible for moving force such a giant boulder in present position. This study analysis that, the normal river flow, such as the Seti River, lacks the kinetic energy required to transport Bhimdhunga. Instead, a powerful natural event—such as a glacial outburst flood, an earthquake-triggered landslide, or a massive debris flow—was likely responsible. The force required to move the boulder was calculated to be around 756 million Newtons, far exceeding what a typical river current could generate. This suggests that glacial movement during the Ice Age transported Bhimdhunga, along with other large boulders like Chipledhunga in plain area. The study highlights that Bhimdhunga serves as an important geological marker, reflecting the fluvio glacial forces that shaped Pokhara Valley. The findings of this research reinforce the importance of shaping the Himalayan landscape and provide new insights into the tectonic and climatic history of Pokhara Valley. The study underscores the need to preserve such natural landmarks, as they offer valuable evidence of past geological transformations and help expand researchers understanding of tectonic and glacial dynamics in the region.